Shape-stabilized phase change materials: Performance of simple physical blending synthesis and the potential of coconut based materials. (25th August 2022) - Muchtar, Ahmad Rifqi; Hassam, Christopher L.; Srinivasan, Bhuvanesh; Berthebaud, David; Mori, Takao; Soelami, Nugroho; Yuliarto, Brian
Abstract: This research reports, for the first time, the combination of food-grade coconut oil and coconut shell-based activated carbon as precursors for the synthesis of bio-based shape-stabilized phase change materials (bioSSPCM). Despite its low melting enthalpy, simple physical blending by heating and mixing is found to be a very reliable preparation method for the completely coconut-based materials, producing a thermally stable bioSSPCM with anti-leakage. No difference between food grade and analytical grade coconut oil, in terms of its application for SSPCMs, was evident. Further, comparing the performance of coconut oil against octadecane, a conventional phase change material, it was found that with the same synthesis conditions, the coconut oil exhibited improved stability, with less leakage after phase change cycling. Highlights: Synthesis of SSPCM without the use of costly equipment or additional solvents Coconut materials based SSPCM with an enthalpy of 42.6 J/s. Coconut oil shows better anti-leakage properties compared to octadecane. Increase of thermal conductivity due to activated carbon More uniform temperature distribution and faster response time